Discount window borrowing after 2003: The explicit reduction in implicit costs - Artuç, Erhan; Demiralp, Selva (Journal of Banking & Finance, 2010)
In 2003, the Federal Reserve introduced primary credit as its main discount window lending program. This program replaced the adjustment credit program, which, subject to a number of restrictions, had generated a stigma associated with borrowing from the Federal Reserve. Lessening the stigma of borrowing was viewed as essential for reducing the reluctance to borrow from the Federal Reserve. We develop a structural model of daily borrowing. Using this model, we estimate the implicit cost associated with borrowing. Our results suggest that the stigma of borrowing is significantly reduced.